Pytanie o „światło wiary" w perspektywie myśli Tomasza z Akwinu - Salij, Jacek (Poznańskie Studia Teologiczne, 2014)
It seems that one of the reasons why the term “the light of Faith” occurs rarely in modern Church teaching is that today we do not distinguish clearly enough faith from convictions and worldview. In terms of St. Thomas Aquinas the concept of “the light of Faith” is something more than an accidental metaphor. It occupies a precise position in a series of three hierarchical metaphors that represent three radically different situations of our access to the truth. The article explains what in the texts of Aquinas is the light of reason, the light of Faith and the light of glory.